2015
DOI: 10.1371/journal.pone.0124888
|View full text |Cite
|
Sign up to set email alerts
|

The PGE2/IL-10 Axis Determines Susceptibility of B-1 Cell-Derived Phagocytes (B-1CDP) to Leishmania major Infection

Abstract: B-1 cells can be differentiated from B-2 cells because they are predominantly located in the peritoneal and pleural cavities and have distinct phenotypic patterns and activation properties. A mononuclear phagocyte derived from B-1 cells (B-1CDP) has been described. As the B-1CDP cells migrate to inflammatory/infectious sites and exhibit phagocytic capacity, the microbicidal ability of these cells was investigated using the Leishmania major infection model in vitro. The data obtained in this study demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 68 publications
(66 reference statements)
4
58
0
Order By: Relevance
“…B‐1 cells‐derived phagocytes (B‐1 CDP) are capable of internalizing certain pathogens, including L. major . We evaluated whether this cell population was also permissive for infection with L. (L.) amazonensis promastigotes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…B‐1 cells‐derived phagocytes (B‐1 CDP) are capable of internalizing certain pathogens, including L. major . We evaluated whether this cell population was also permissive for infection with L. (L.) amazonensis promastigotes.…”
Section: Resultsmentioning
confidence: 99%
“…These cells had a significantly higher phagocytic index compared to peritoneal or medullar macrophages at 16 and 24 h. Few reports have described the phagocytosis of pathogens by B‐1 cells, so little knowledge is available concerning the functions and consequences of this process in immunity (especially in infectious diseases). B‐1 cells were able to differentiate into phagocytes that were highly susceptible to in vitro infection by Cryptococcus neoformans , Coxiella burnetii and L. major . However, the mechanisms used by these pathogens to enter B‐1 cells appeared to be different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that IL-10-derived from B cells is capable to promote the development of suppressive responses associated with susceptibility to infection (Bankoti et al, 2012; Arcanjo et al, 2015). However, the identification of the B cell population involved in the susceptibility to VL is still vague and needs further studies.…”
Section: Introductionmentioning
confidence: 99%